Impact of Public Distribution System on Traditional Food Habits of Rural People - Shashidhar, K.C.; swamy, A.S. Kumarswamy; Shivamurthy, M. (Indian Journal of Extension Education, 2010)
Rapid dietary changes among rural people worldwide are posing threats to the food pattern and the traditional knowledge was essentially required for maintenance of traditional food habit. This study was conducted to know the potential reasons for change in the traditional food habit in villages. It was conducted in a typical Indian village in Shimoga district of Karnataka State in South India. Results indicated that though increase in income was a major reason for change in the food habit, people changed their food habits even without any significant increase in income. This change was attributed to the introduction of Public Distribution System. The Public Distribution System was a critical resource for the food security of the poor people. The results of this study would help to add new dimensions to Public.